Minimum wages and vocational training incentives in Germany - Kim Leonie Kellermann (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
We examine the impact of sector-specific minimum wages in Germany on the willingness of youths to undergo vocational training. The theoretical intuition on the impact of wage floors on education is ambiguous. On the one hand, they raise the opportunity cost of education and prevent further skill accumulation. On the other hand, they lower the employment probability of unskilled workers, promoting additional training. Employing a mixed logit model, we estimate the probability of opting for an apprenticeship for a GSOEP-based sample of youths aged 17 to 24. Unlike the evidence from other countries, we find that increasing sectoral wage floors have a positive effect on training probabilities. Due to binding minimum wages, the demand for unskilled workers declines which lowers the opportunity cost of education. High requirements with regard to professional skills reinforce the effect.
Keywords: C33; I21; I28; J24; 330; minimum wages; education; vocational training; occupational choice; discrete choice